2001
DOI: 10.2169/internalmedicine.40.862
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Crescents and Segmental Glomerular Necrosis in IgA Nephropathy Are Indicative of the Beneficial Effects of Corticosteroid Therapy.

Abstract: Objective Recent reports have revealed that corticosteroid (PSL) therapy has a long-term beneficial effect for stabilization of renal function in progressive IgA nephropathy.Patients and methods Weanalyzed serum creatinine (Cr), daily proteinuria and the results of other routine laboratory examinations during a short-term course of PSL therapy in 28 cases of progressive IgA nephropathy. The cases were divided into two groups according to changes in renal function during the PSL treatment period: group I (15 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…They suggested that steroid therapy could delay the progression to endstage renal failure (ESRD). Tomiyoshi et al 10 also suggested that steroid therapy was effective for IgAN patients who showed a high percentage of cellular and fibrocellular crescents, although the Ccr in their patients was under 70 ml/min.…”
Section: Discussionmentioning
confidence: 97%
“…They suggested that steroid therapy could delay the progression to endstage renal failure (ESRD). Tomiyoshi et al 10 also suggested that steroid therapy was effective for IgAN patients who showed a high percentage of cellular and fibrocellular crescents, although the Ccr in their patients was under 70 ml/min.…”
Section: Discussionmentioning
confidence: 97%
“…The pathological features have been proved as risk factors for progression of IgAN and were important factors for guiding treatment [5,6,21,22] . Most of the research found SGN accompanied by crescents were indicative of the beneficial effects of corticosteroid therapy [13][14][15] . In D'Amico's research, about IgAN with SGN, the effect of corticosteroid was not defined [21] .…”
Section: Discussionmentioning
confidence: 99%
“…But the significance of SGN was not included in all the classifications. Most of the researches about SGN in IgAN were about cellular crescents accompanied with SGN [13][14][15] . However, we have observed a number of patients who have presented with slight histopathological damage despite SGN.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that steroid therapy could delay the progression to end-stage renal failure. Tomiyoshi et al [15] suggested that steroid therapy (40-50 mg/day as an initial dose) was effective for IgAN patients who showed a high percentage of cellular and fibrocellular crescents and/or segmental glomerular sclerosis, although their Ccr was under 70 ml/min. We also reported the effectiveness of steroid therapy for advanced IgAN patients with reduced renal function [16].…”
Section: Discussionmentioning
confidence: 99%